The activist collector : Lida Clanton Broner's 1938 journey from Newark to South Africa - Clarke, Christa; Harrison, Linda C.; Walter de Gruyter & Co. (Newark, New Jersey : Newark Museum of Art ; New Brunswick, New Jersey : Rutgers University Press, 2022)
"After twenty-eight years of desire and determination, I have visited Africa, the land of my forefathers." So wrote Lida Clanton Broner (1895-1982), an African American housekeeper and hairstylist from Newark, New Jersey, upon her return from an extraordinary nine-month journey to South Africa in 1939. This epic trip was motivated not only by Broner's sense of ancestral heritage, but also a grassroots resolve to connect the socio-political concerns of African Americans with those of black South Africans under the segregationist policies of the time. During her travels, this woman of modest means circulated among South Africa's black intellectual elite, including many leaders of South Africa's freedom struggle. Her lectures at black schools on "race consciousness and race pride" had a decidedly political bent, even as she was presented as an "American beauty specialist." How did Broner--a working class mother--come to be a globally connected activist? What were her experiences as an African American woman in segregated South Africa and how did she further her work after her return? Broner's remarkable story is the subject of this book, which draws upon a deep visual and document-ary record now held in the collection of the Newark Museum. This extraordinary archive includes more than 150 objects, ranging from beadwork and pottery to mission school crafts, acquired by Broner in South Africa, along with her diary, correspondence, scrapbooks, and hundreds of photographs with handwritten notations.
Prologue : "Desire and determination" -- A transatlantic friendship -- From personal pilgrimage to political purpose -- "Welcome to Africa!" -- Onward and inward to the Transvaal and Natal -- Return to the eastern Cape and voyage home -- Activist exhibitions -- The Newark Museum and beyond -- Epilogue: Mother of the Oceans.
Includes bibliographical references.
Description based on print version record.
JSTOR
Keywords: Broner, Lida Clanton, -- 1895-1982 -- Art collections; Newark Museum; Newark Museum; Art, African -- Collectors and collecting -- United States; Handicraft -- Collectors and collecting -- New Jersey -- Newark; Handicraft -- Collectors and collecting -- South Africa; African Americans -- New Jersey -- Newark -- Biography; Women -- New Jersey -- Newark -- Biography; Newark (N.J.) -- Biography; Art africain -- Collectionneurs et collections -- États-Unis.; Artisanat -- Collectionneurs et collections -- New Jersey -- Newark; Artisanat -- Collectionneurs et collections -- Afrique du Sud; Noirs américains -- New Jersey -- Newark -- Biographies; Femmes -- New Jersey -- Newark -- Biographies; ART / General; African Americans; Art, African -- Collectors and collecting; Art -- Private collections; Women; New Jersey -- Newark; South Africa; United States; history, black, african american, south africa, american, art, art collection, activism, race, culture, 1930s, segregation, racism, discrimination, biography, lida clanton broner; Biographies